2007
DOI: 10.1292/jvms.69.77
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Circulating Vascular Endothelial Growth Factor in Dogs with Mammary Gland Tumors

Abstract: ABSTRACT. Increase in circulating vascular endothelial growth factor (VEGF) is suggested as a prognostic indicator in human patients with malignant tumors. The purpose of this study was to evaluate the clinical significance of circulating VEGF in dogs with mammary gland tumors (MGT). Both plasma and serum VEGF were significantly higher in dogs with MGT when compared with those in the healthy dogs. In dogs with MGT, the plasma and serum VEGF of the malignant group increased significantly compared with those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…Meanwhile, Troy et al (2006), when studying VEGF in dogs suffering from malignant tumours, obtained results between 2.5 pg/mL and as high as 274 pg/mL. Also, Kato et al (2007) tested VEGF using a Human VEGF Quantikine ELISA Kit. They confirmed elevation of VEGF levels in the blood serum of dogs diagnosed with malignant mammary gland tumours, with the recorded values ranging from not detectable to 992.9 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Troy et al (2006), when studying VEGF in dogs suffering from malignant tumours, obtained results between 2.5 pg/mL and as high as 274 pg/mL. Also, Kato et al (2007) tested VEGF using a Human VEGF Quantikine ELISA Kit. They confirmed elevation of VEGF levels in the blood serum of dogs diagnosed with malignant mammary gland tumours, with the recorded values ranging from not detectable to 992.9 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…skin and subcutaneous tissue cancer as well as mammary gland cancer. It has been demonstrated that, in such cases, VEGF overexpression can indicate a malignant course of the disease and a higher potential for metastasis (Kato et al, 2007;Sobczyńska-Rak, 2012).…”
mentioning
confidence: 99%
“…Only when VEGF is expressed in MMTV-myc mice does metastatic disease ensue, characterized by high degree of vascularity and increased synthesis of extracellular matrix proteins, such as type I collagen, fibronection, and tenascin C. 23 This is supported by Kato et al, who observed an increase in plasma and serum VEGF in dogs with mammary tumors. 127 Qiu et al also found VEGF overexpression in spontaneous canine malignant mammary tumors and even more so in their lymph node metastases. 198 Interestingly, the same group showed expression of PTEN to be lower in malignant mammary tumors than in either benign tumors or normal mammary gland and even lower in lymph nodes metastases.…”
Section: Vascular Endothelial Growth Factorsmentioning
confidence: 94%
“…By considering canine mammary tumors, kato et al (30) found higher serum VEGF levels in female dogs with malignant tumors compared to female dogs with benign tumors, as well as in female dogs that had lung metastasis after tumor excision. Marked VEGF mitogenic properties led to an increase in the permeability of blood vessels, allowing cancer cells to pass through to extravascular spaces and form distant metastases (50).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF stimulates endo thelial cell proliferation, migration and capillary tube formation (28,(30)(31). Tumor growth through angiogenesis is directly correlated with VEGF expression in breast cancer (15,16,(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%